Lifestyle determinants of serum insulin-like growth-factor-I (IGF-I), C-peptide and hormone binding protein levels in British women. - Allen, N; Appleby, P; Kaaks, R; Rinaldi, S; Davey, G; Key, T (2003)
OBJECTIVE: This study aims to identify the lifestyle determinants of insulin-like growth factor-I (IGF-I) and its main binding proteins (IGFBPs), C-peptide, and sex hormone-binding globulin (SHBG) to help elucidate the mechanism through which lifestyle factors may affect cancer risk. METHODS: This study is based on a sample of 292 British women, aged 20-70 years, whose lifestyle characteristics were assessed using a self-administered questionnaire and whose serum hormone concentrations were measured using immunoassays. RESULTS: Age was a strong determinant of both IGF-I and IGFBP levels; women aged 65-70 years had significantly lower IGF-I and IGFBP-3 concentrations and significantly higher IGFBP-1 and IGFBP-2 concentrations than women aged 20-24 years. Body mass index (BMI) was not strongly associated with IGF-I, although women with a BMI of 26-27.9 kg/m2 had a higher IGF-I concentration compared with both lean (BMI <20 kg/m2) and obese (BMI 30+ kg/m2) women. However, obese women had a significantly higher C-peptide and IGFBP-3 concentration and a significantly lower IGFBP-1, IGFBP-2, and SHBG concentration compared with lean women. Increasing vigorous exercise was associated with a significantly lower C-peptide concentration and increasing leisure-time activity was associated with a significantly higher IGFBP-1 concentration. Other lifestyle factors such as job activity, smoking, and reproductive factors were not associated with any hormone. CONCLUSIONS: Our data show that age is a major determinant of both IGF-I and its main binding proteins in women. BMI has strong effects on IGFBPs, C-peptide, and SHBG, but its effects on IGF-I remain unclear. The possible effect of physical activity on IGFBP-1 requires further investigation.